2021
DOI: 10.1186/s41983-021-00278-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of repetitive transcranial magnetic stimulation in treating patients with chronic daily headache

Abstract: Background Headache is the most common pain disorder, affecting around 66% of the global population. This study aimed to investigate the efficacy of high-frequency repetitive transcranial magnetic stimulation (rTMS) in treating patients with primary chronic daily headaches (chronic tension-type headache and chronic migraine). Methods Twenty-seven patients participated in the study, divided into 2 groups: a study group (16 patients) and a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…All but one study included patients with chronic migraine only. The study by AbdElkader et al 26 included patients with chronic daily headaches together with migraine. All eight RCTs have concluded that rTMS is effective treatment approach for migraine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All but one study included patients with chronic migraine only. The study by AbdElkader et al 26 included patients with chronic daily headaches together with migraine. All eight RCTs have concluded that rTMS is effective treatment approach for migraine.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria were similar for all the studies with greater diversity in exclusion criteria especially concerning the presence of depression. Of the included studies, three have explicitly excluded patients with depression 26,27,29 and one study has reported absence of patients with clinical depression 28 . In addition, three RCTs have excluded patients with severe psychiatric comorbidity 31–33 .…”
Section: Resultsmentioning
confidence: 99%